Growth performance, biomass and phytoextraction efficiency of Acacia mangium and Melaleuca cajuputi in remediating heavy metal contaminated soil - Nik Jaafar, Nik Mohd Shibli; Nik Ab. Majid, Nik Muhamad; Mohamed Shazili, Noor Azhar; Abdu, Arifin (Science Publication, 2013)
Heavy metals are very toxic and soil contaminated with sewage sludge urgently need remediation in order to avoid related health hazards. Phytoremediation is a low cost and reliable technique to remediate heavy metal contamination. However phytoremediation using timber species was rarely reported and its efficiency was questionable. A field study was conducted to examine the efficiency of two timber species namely Acacia mangium and Melaleuca cajuputi in phytoextraction of Zn, Cu and Cd from contaminated soil. Two hundred of A. mangium and M. cajuputi were planted on sewage sludge disposal site and the growth was recorded for 12 months before at the end total biomass of each species was determined. Results show in 12 months, about 72 and 4 t ha−1 of aboveground biomass can be produced by A. mangium and M. cajuputi, respectively. Both species show potential for phytoremediation, however A. mangium is more efficient compared to M. cajuputi where efficiency of A. mangium to remove Zn was 24.4, 6.2 for Cu and 9.5% for Cd. As for M. cajuputi the efficiency was 1.3, 0.3 and 0.14% for Zn, Cu and Cd, respectively. It is projected that A. mangium require 5, 17 and 20 years to remove 79.82 kg ha−1 of Zn, 46.94 kg ha−1 of Cu and 2.33 kg ha−1 of Cd, respectively.